CONVERSATIONAL IMPLICATURE OF HKBP NOMMENSEN MEDAN STUDENTS IN DAILY CONVERSATION - Kirsten Nia T Silangit; Fenty Debora Napitupulu; Harpen H. P. Silitonga (Jurnal Scientia, 2023)
This research discusses an overview of student conversational implicatures when students have conversations. This study uses a qualitative descriptive research method. The data sources in this study were obtained from students' daily conversations around the campus environment. This research used the Grice and Yule theories. Data collection techniques in this study used the recording method. There are several ways to collect data, have short conversations, the author joins the conversation, the author hears the conversation and records it. The results of the study are: conversational implicatures found in students' speeches in student conversations are categorized into four types of conversational implicatures, namely general conversational implicatures, particularized conversational implicatures, scalar implicatures and porpeties implicatures. Generalized conversational implicature is most used in students' daily conversations. Therefore, students unconsciously use implicatures in their daily conversations. Based on the research findings, the researcher suggests to English students to provide basic knowledge in conversational implicatures.